Comparison of Dispute Resolution in General Elections in Indonesia and Thailand - Saputra, Darwin; Amiludin, Amiludin; Ahmad, Dwi Nur Fauziah; Razif, Imran Bukhari (Indonesia Law Reform Journal, 2024)
The history of general elections in Indonesia began in 1955 with the implementation of a Proportional Representation system, allowing voters to directly elect candidates or parties. This system underwent modifications over time, including the adoption of an open-list system in 2004. The enactment of Law No. 7 of 2017 subsequently regulated the conduct of general elections in Indonesia, emphasizing principles such as direct, general, free, secret, fair, and honest elections. In Thailand, the history of general elections commenced following the 1932 revolution that ended absolute monarchy. Despite this, Thailand has experienced numerous military coups affecting its political dynamics, notably in 2006 and 2014, sparking debates among opposing political factions. This study employs a normative and legal approach to analyze the dispute resolution systems of general elections in Indonesia, contrasting them with Thailand's specialized commission approach for similar matters. In Indonesia, the resolution of election disputes is governed by Law No. 7 of 2017, with oversight bodies including the General Election Commission and the Election Supervisory Board. Conversely, Thailand's Election Commission of Thailand plays a crucial role in resolving election disputes in accordance with the constitution. Both countries adopt different approaches in handling election disputes; Indonesia relies on judicial bodies such as the Administrative Court and the Supreme Court, whereas Thailand employs the Election Commission of Thailand as a non-judicial institution with broad authority in addressing electoral law violations. Abstrak Sejarah Pemilihan Umum di Indonesia dimulai pada tahun 1955 dengan menggunakan Sistem Proporsional, di mana pemilih dapat memilih calon secara langsung atau partai. Sistem ini mengalami modifikasi dari waktu ke waktu, termasuk penerapan stelsel daftar terbuka pada tahun 2004. Undang-Undang No. 7 Tahun 2017 kemudian mengatur pelaksanaan pemilihan umum dengan prinsip-prinsip seperti langsung, umum, bebas, rahasia, jujur, dan adil. Di Thailand, sejarah pemilihan umum dimulai setelah revolusi tahun 1932 yang mengakhiri monarki absolut. Meskipun demikian, Thailand mengalami banyak kudeta militer yang mempengaruhi dinamika politiknya, termasuk kudeta pada tahun 2006 dan 2014 yang melibatkan perdebatan antara faksi-faksi politik yang berseberangan. Penelitian ini menggunakan pendekatan normatif dan perundang-undangan untuk menganalisis sistem penanganan sengketa pemilihan umum di Indonesia, dibandingkan dengan Thailand yang memiliki pendekatan komisi khusus untuk hal serupa. Penyelesaian sengketa pemilihan umum di Indonesia diatur dalam Undang-Undang No. 7 Tahun 2017, dengan badan penyelesaian termasuk Komisi Pemilihan Umum dan Badan Pengawas Pemilihan umum. Di Thailand, Election Commission of Thailand memiliki peran penting dalam menyelesaikan sengketa pemilihan umum sesuai dengan konstitusi. Kedua negara memiliki pendekatan yang berbeda dalam menangani sengketa pemilihan umum, Indonesia melalui badan peradilan seperti Pengadilan Tata Usaha Negara dan Mahkamah Agung, sedangkan Thailand melalui Election Commission of Thailand sebagai lembaga non-peradilan yang memiliki kewenangan luas dalam menangani pelanggaran undang-undang pemilihan umum.